Job quality in industries dependent on United States demand for Canadian exports - Marc Frenette; Tahsin Mehdi; René Morissette (Economic and Social Reports)
While it is challenging to estimate the number of job losses that may be associated with U.S. tariffs, it is possible to describe the quality of jobs at risk of being affected by a decline in U.S. demand for Canadian products. This article addresses this issue by examining a multitude of job quality measures in industries dependent on U.S. demand for Canadian exports.